Annexin-A1: Therapeutic Potential in Microvascular Disease - Purvis, Gareth S. D.; Solito, Egle; Thiemermann, Christoph (Frontiers in Immunology, 2019)
Annexin-A1 (ANXA1) was first discovered in the early 1980’s as a protein, which mediates (some of the) anti-inflammatory effects of glucocorticoids. Subsequently, the role of ANXA1 in inflammation has been extensively studied. The biology of ANXA1 is complex and it has many different roles in both health and disease. Its effects as a potent endogenous anti-inflammatory mediator are well described in both acute and chronic inflammation and its role in activating the pro-resolution phase receptor, FPR2, has been described and is now being exploited for therapeutic benefit. In the present mini review, we will endeavour to give an overview of ANXA1 biology in relation to inflammation and functions that mediate pro-resolution that are independent of glucocorticoid induction. We will focus on the role of ANXA1 in diseases with a large inflammatory component focusing on diabetes and microvascular disease. Finally, we will explore the possibility of exploiting ANXA1 as a novel therapeutic target in diabetes and the treatment of microvascular disease.